Pastoral Counseling Effective from a Christian Perspective (An Introduction to Today's Ministry) - Gilbert Emanuel Lumoindong; Junifrius Gultom (Budapest International Research and Critics University, 2022)
Counseling is an inseparable part of carrying out church duties, because the task of counseling involves the duties of the church. This paper discusses about counseling carried out by God's servants, in this case the Pastor. The lack of several churches in practicing counseling services encourages the author to offer suggestions in the fruit of this paper to serve as guidelines, at least as motivation for readers or enthusiasts of problems related to this. Thus, church leaders need to revive this activity in their pastoral ministry. The method used by the author in exploring this paper is by taking a qualitative approach with reference to the literature or literature obtained from a collection of related sources, in this case Pastoral Counseling, namely by correlating the perspectives of experts. Also collect facts and describe cases.